Cerebral ischaemia and matrix metalloproteinase‐9 modulate the angiogenic function of early and late outgrowth endothelial progenitor cells. Issue 12 (15th August 2013) - Morancho, Anna; Hernández‐Guillamon, Mar; Boada, Cristina; Barceló, Verónica; Giralt, Dolors; Ortega, Laura; Montaner, Joan; Rosell, Anna
Abstract The enhancement of endogenous angiogenesis after stroke will be critical in neurorepair therapies where endothelial progenitor cells (EPCs) might be key players. Our aim was to determine the influence of cerebral ischaemia and the role of matrix metalloproteinase‐9 (MMP‐9) on the angiogenic function of EPCs. Permanent focal cerebral ischaemia was induced by middle cerebral artery (MCA) occlusion in MMP‐9/knockout (MMP‐9/KO) and wild‐type (WT) mice. EPCs were obtained for cell counting after ischaemia (6 and 24 hrs) and in control animals. Matrigel™ assays and time‐lapse imaging were conducted to monitor angiogenic function of WT and MMP9‐deficient EPCs or after treatment with MMP‐9 inhibitors. Focal cerebral ischaemia increased the number of early EPCs, while MMP‐9 deficiency decreased their number in non‐ischaemic mice and delayed their release after ischaemia. Late outgrowth endothelial cells (OECs) from ischaemic mice shaped more vessel structures than controls, while MMP‐9 deficiency reduced the angiogenic abilities of OECs to form vascular networks, in vitro. Treatment with the MMP inhibitor GM6001 and the specific MMP‐9 inhibitor I also decreased the number of vessel structures shaped by both human and mouse WT OECs, while exogenous MMP‐9 could not revert the impaired angiogenic function in MMP‐9/KO OECs. Finally, time‐lapse imaging showed that the extension of vascular networks was influenced by cerebral ischaemia and MMP‐9 deficiency early during the vascular network formation followed by a dynamic vessel remodelling. We conclude that focal cerebral ischaemia triggers the angiogenic responses of EPCs, while MMP‐9 plays a key role in the formation of vascular networks by EPCs.